Agreement between Powertap, Quarq and Stages power meters for cross-country mountain biking - Miller, M. C.; Macdermid, P. W.; Fink, P. W.; Stannard, S. R. (Sports Technology, 2015)
Advances in technology have made the use of a variety of power meters ubiquitous in road cycling along with an ever-increasing popularity during mountain biking. This study compared data from one bicycle using three power meters: Stages (non-driveside crank arm); Quarq (chainring spider); and Powertap (rear-wheel hub). While no differences (p?>?.05) between power meters were present during treadmill riding at high or low cadences, dissimilarities for both power (W) and cadence (rpm) were apparent during actual cross-country mountain bike riding. Frequency distribution and analysis of coasting indicate that the Stages records more time (p < .001) at zero watts (6.9 ± 3.3 s) and zero cadence (6.9 ± 3.3 s) compared with Quarq (W = 3.3 ± 1.5 s, rpm = .8?±?.7 s) and Powertap (W = 1.1 ± .8 s, rpm = 3.0 ± 1.2 s). Consequently, significant interactions (power meter × terrain, p = .0351) and main effects (power meter p < .0001, and terrain p < .0001) for power output were present and included: uphill (317.5 ± 50.7, 340.8 ± 52.6, 327.3 ± 48.6 W); downhill (127.6 ± 12.3, 147.4 ± 23.8, 160.1 ± 24.0 W); and flat (201.1 ± 21.6, 225.2 ± 27.2, 224.0 ± 29.6 W) for the Stages, Quarq and Powertap, respectively. It is likely that accelerometry (Stages) compared with reed switch (Powertap and Quarq) technology to determine cadence, resulted in the discrepancies between power meters. However, while the reliability of the different methods appears acceptable for intermittent exercise such as cross-country mountain biking, the validity of each in such a situation requires confirming.